PENGARUH INNOVATION DAN SERVICE QUALITY MELALUI CUSTOMER TRUST TERHADAP CUSTOMER SATISFACTION DI PAMELLA SUPERMARKET JL. KUSUMANEGARA NO.141 YOGYAKARTA - Devi Eka Sari (JURNAL EKOBIS DEWANTARA, 2018)
This research is conducted to know the influence of innovation and service quality to customer satisfaction through customer trust at Pamella Supermarket Yogyakarta. Research location in Yogyakarta. Population of this research is customer living in Yogyakarta. The sample of 100 respondents taken using accidental sampling technique of data collection method using questioner. Data analysis used is descriptive analysis, multiple regression analysis and path analysis. The results of this study indicate that innovation has significant effect on customer trust; service quality have significant influence to customer trust, innovation has significant effect to customer satisfaction, serive quality has significant effect to customer satisfaction and customer trust have significant effect to customer satisfaction.